High-Efficient Low-Cost Photovoltaics - Petrova-Koch, Vesselinka (Springer, 2017)
A bird's-eye view of the development and problems of recent photovoltaic cells and systems and prospects for Si feedstock is presented. High-efficient low-cost PV modules, making use of novel efficient solar cells (based on c-Si or III-V materials), and low cost solar concentrators are in the focus of this book. Recent developments of organic photovoltaics, which is expected to overcome its difficulties and to enter the market soon, are also included.